Standardization of Phyllanthus niruri and Sonchus arvensis as Components of Scientific Jamu - Nikmatul Ikhrom Eka Jayani; Alfian Hendra Krisnawan; Nina Dewi Oktaviyanti; Kartini Kartini (Majalah Obat Tradisional, 2020)
Saintifikasi Jamu, or the scientific investigation of Jamu, is an evidence-based process to ensure the safety and efficacy of herbal medicine through health service research. Jamu has been empirically explored as a composition of various crude drugs, hence called as Scientific Jamu. Phyllanthus niruri and Sonchus arvensis are two of the 30 medicinal plants processed into Scientific Jamu. Components of the Scientific Jamu are standardized to ensure that these materials meet the predefined quality. This study was aimed to determine the specific parameters (macroscopic, microscopic, total flavonoid content, water-soluble extract content, and ethanol-soluble extract content) and non-specific parameters (loss on drying, total ash content, and acid insoluble ash content) of Phyllanthus niruri and Sonchus arvensis collected from Batu, Tawangmangu, and Bogor. The methods of the determination referred to the Indonesian Herbal Pharmacopoeia 1st Edition (2008). The results showed that Phyllanthus niruri and Sonchus arvensis from the three places did not meet the standard requirement.